THE ROLE OF EMOTIONAL INTELLIGENCE IN ENHANCING LEARNING AND TEACHING EFFECTIVENESS IN THE EDUCATION SECTOR - Singh, Rajbir; Deveshwar, Aarti; Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotional Intelligence is the capacity to comprehend both one's own emotions and those of others. According to the idea of emotional intelligence, people need to be self-aware enough to identify and control their emotion. Emotional intelligence (EI) enables people to modify their behavior toward their work environment and all tasks that are allocated in accordance with the requirements. The main aim of the paper is to study the role of Emotional Intelligence in Teacher’s Job Performance in Education Sector and to define how Emotional Intelligence influences the Student’s Performance and how it relates to other psychological factors. It has been discovered that emotional intelligence is essential for people to perform well, which in turn promotes organizational effectiveness. In the field of education, the study seeks to comprehend the function of emotional intelligence & how it affects job performance. When it comes to the education sector, emotional intelligence has an influence on employee’s job performance. Exceptional performance requires teachers who possess a high degree of emotional intelligence. According to this paper, Educational institutions can improve their skills, become more knowledge-oriented, responsible, and creative by developing their emotional intelligence. It comes to the conclusion that the process of knowledge generation, acquisition, and sharing is positively impacted by emotional intelligence.